2004
DOI: 10.1016/s0002-9440(10)63291-9
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Accumulation and Neuroprotection in Hypoxic Brain Damage

Abstract: The function of the normal conformational isoform of prion protein, PrP(C), remains unclear although lines of research have suggested a role in the cellular response to oxidative stress. Here we investigate the expression of PrP(C) in hypoxic brain tissues to examine whether PrP(C) is in part regulated by neuronal stress. Cases of adult cerebral ischemia and perinatal hypoxic-ischemic injury in humans were compared with control tissues. PrP(C) immunoreactivity accumulates within neuronal processes in the penum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
174
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(198 citation statements)
references
References 45 publications
(43 reference statements)
13
174
1
8
Order By: Relevance
“…If, in contrast to our present uniformly negative observations, PrP Sc or PrP res were to be detected in human amyloidotic tissues, extensive control studies with human tissues containing other, non-amyloid, pathologies would be essential to determine whether there was any specific relationship with amyloidosis, since over-expression of PrP may be a general response to tissue pathology. Indeed, we have previously reported that prion protein is present in the penumbra of brain infarcts, but this results from overexpression of PrP C rather than local accumulation of PrP Sc [38].…”
Section: Codon 129 Genotypementioning
confidence: 94%
“…If, in contrast to our present uniformly negative observations, PrP Sc or PrP res were to be detected in human amyloidotic tissues, extensive control studies with human tissues containing other, non-amyloid, pathologies would be essential to determine whether there was any specific relationship with amyloidosis, since over-expression of PrP may be a general response to tissue pathology. Indeed, we have previously reported that prion protein is present in the penumbra of brain infarcts, but this results from overexpression of PrP C rather than local accumulation of PrP Sc [38].…”
Section: Codon 129 Genotypementioning
confidence: 94%
“…In addition, polymorphisms in the regulatory region of PRNP may present a risk for Creutzfeldt-Jakob disease (6,7). Furthermore, accruing evidence implicates the normal cellular PrP in a number of essential cellular functions including neuroprotection against oxidative stress (8,9), copper toxicity (10), Bax-mediated cell death (11), and ischemia (12)(13)(14)(15). There is also evidence that PrP participates in normal synaptic function (16) and myelination (17,18).…”
mentioning
confidence: 99%
“…In the last decade a diverse range of functions has been attributed to the native PrP C protein, such as neuroprotection against cellular and systemic insults, neuritogenesis, neuronal plasticity and excitability, and memory formation and consolidation (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Noteworthy, PrP C mutations associated to CJD, fatal familial insomnia, and Gerstmann-Straussler-Scheinker disease decrease or abolish the anti-bax function in primary human neurons and breast cancer cell lines promoting programmed cell death (34).…”
mentioning
confidence: 99%